Salicylic Acid Signalling in Plants - Janda, Tibor; Pál, Magda; Szalai, Gabriella (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Although the role of salicylic acid (SA) in plant physiological processes has been widely studied for a long time, many open questions remain several fields. The importance of SA synthesis is illustrated by the four review papers published in this Special Issue that represent a wide range of approaches, indicating that a growing body of evidence needs to be summarized in a thought-provoking manner. The investigations presented in the six original studies extend upon the understanding of the involvement of SA in anthracnose infection and light-dependent cold acclimation, highlighting the use of SA mutant Arabidopsis plants. The studies also focused on the application of novel SA analogs or SA in combination with Rhizobacteria inoculation. We hope that the four reviews and six studies provide a deeper understanding of the role of SA and its complex tasks, as well as a new direction for research to address gaps and open questions, including both at the metabolite and gene expression levels, in the use of agriculturally important crop or mutant model plants, and in both basic research and practical applications.